Consensus on post COVID in the Spanish national health system: Results of the CIBERPOSTCOVID eDelphi study - Marta Torres; Vicky Serra-Sutton; Joan B. Soriano; Montse Ferrer; Alex Trejo; Fernando G. Benavides; Blanca Lumbreras; Beatriz Pérez-Gómez; José I. Pijoan; Josep M. Monguet; Ferran Barbé; Marina Pollán; et al. (Elsevier, 2023)
Background: In 2021, the Spanish Ministry of Health launched the CIBERPOSTCOVID project to establish what post COVID was. The present study reports the level of agreement among stakeholders on post COVID and its clinical and diagnostic characteristics in the Spanish health system. Methods: The agreement on post COVID among clinicians, public health managers, researchers and patients' representatives was explored in a real-time, asynchronous online Delphi. In a two-wave consensus, respondents rated from 1 (total disagreement) to 6 (total agreement) 67 statements related to terminology, duration, etiology, symptoms, impact on quality of life, severity, elements to facilitate diagnosis, applicability in the pediatric population, and risk factors. Consensus was reached when 70 % of ratings for a statement were 5 or 6, with an interquartile range equal or less than 1. Findings: A total of 333 professionals and patients participated in this eDelphi study. There was agreement that post COVID was "a set of multi-organic symptoms that persist or fluctuate after acute COVID-19 infection and are not attributable to other causes" with a minimum duration of 3 months. The highest levels of agreement were found in the most frequent symptoms and its impacts on everyday activities. Aspects related to the diagnostic process and the measurement of its severity reached a lower level of consensus. There was agreement on the need to rule out previous health problems and assess severity using validated functional scales. However, no agreement was reached on the risk factors or specific features in the pediatric population. Interpretation: This policy-based consensus study has allowed the characterization of post COVID generating collective intelligence and has contributed to an operational definition applicable in clinical practice, health services management and useful for research purposes in Spain and abroad. Agreements are consistent with existing evidence and reference institutions at European and international level.